2010
DOI: 10.1258/jrsm.2010.090426
|View full text |Cite
|
Sign up to set email alerts
|

Do stigma and other perceived barriers to mental health care differ across Armed Forces?

Abstract: Summary Objectives Military organizations are keen to address barriers to mental health care yet stigma and barriers to care remain little understood, especially potential cultural differences between Armed Forces. The aim of this study was to compare data collected by the US, UK, Australian, New Zealand and Canadian militaries using Hoge et al.'s perceived stigma and barriers to care measure (Combat duty in Iraq and Afghanistan, mental health problems and barriers to care. New Engl J Med 2004;351:13–22). Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(88 citation statements)
references
References 22 publications
4
84
0
Order By: Relevance
“…However, multinational studies conducted in militaries have reported that stigma is pervasive. 18 A large study reported that active duty soldiers with a mental health problem had significantly higher stigma and significantly lower rates of service utilization than others. 3 A Royal Navy study also found the presence of internal stigma to be substantial and especially for distressed personnel a significant barrier to help.…”
Section: Resultsmentioning
confidence: 99%
“…However, multinational studies conducted in militaries have reported that stigma is pervasive. 18 A large study reported that active duty soldiers with a mental health problem had significantly higher stigma and significantly lower rates of service utilization than others. 3 A Royal Navy study also found the presence of internal stigma to be substantial and especially for distressed personnel a significant barrier to help.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to physical injuries associated with military conflicts, psychological consequences have been recognized following all the major wars in the world (Jones et al, 2002). Military organizations in several nations strived to identify barriers to mental care, especially in delineating the potential stigma and cultural differences between Armed Forces (Gould et al, 2010). Findings indicate that military personnel across all nations underreport mental health issues due to the stigma associated with psychological problems (Gould et al, 2010).…”
Section: Background and Significancementioning
confidence: 99%
“…Military organizations in several nations strived to identify barriers to mental care, especially in delineating the potential stigma and cultural differences between Armed Forces (Gould et al, 2010). Findings indicate that military personnel across all nations underreport mental health issues due to the stigma associated with psychological problems (Gould et al, 2010). Mental illness is perceived to be contradictory to military culture and core military values (Gould et al, 2010) which mandate strength, courage, honor and leadership.…”
Section: Background and Significancementioning
confidence: 99%
See 2 more Smart Citations